An integrated science course moves online: four concurrent perspectives. (19th August 2014) - Major, Amanda E; Chaudhury, S Raj; Gilbertson, Betsy M; King, Jr., David T.; Blessinger, Patrick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The aim of this study is to understand the lived experiences from the voice of the authors (a science professor, an instructional designer, a distance learning doctoral intern, and a distance learning director) in the process of transitioning a face-to-face science course to online modality at a large, research university. Design/methodology/approach The method of this qualitative inquiry involves a personal narrative approach in which the authors reflect on their experiences of this process and analyze it through writing. Findings Our findings examine the challenges of moving a traditional course online and reiterate the value of a team approach to ensure its quality. Our narrative offers clarity to the different phases of such a project and can enhance decision making among those involved in course design and delivery, as well as administrators incentivizing the conversion of traditional courses to the online modality. Practical implications Online education has emerged as a viable solution. The challenges and rewards of transitioning face-to-face courses to distance learning modalities are well documented, even for a senior science educator. Originality/value To support faculty members' transition to online education, universities offer instructional design support, where ideas are exchanged with faculty members to ensure pedagogically sound and engaging distance learning. We conclude with recommendations for both practice and future research in the area of practice and process improvement for diffusion of online courses at traditional universities, one course at a time. This is important to those beginning to transition course offerings online.